The effectiveness of career exploration program for high school students - Lau, P.L.; Khan, A.; Abdullah, H.S.; Chew, F.P. (2011)
The purpose of this study to assess the effects of an 8-week Career exploration Program (CEP) on high school students' career maturity and self-concept in Malaysia. This study was based on a pretest and posttest design using a control group. Data were collected from 69 high school students representing the experimental group and 70 high school students making up the control group. Modes of measurement consisted of the Crites Career Maturity Inventory and the Tennessee Self-Concept Scale. Data for this study were coded numerically and analyzed using analysis of covariance. The results revealed that the sample's career maturity and self-concept improved statistically significant. Discussion and implications for school counselor are discussed.